Risk spillover between Islamic and conventional banking sectors - Dutta, Anupam; Nikkinen, Jussi; Rothovius, Timo (Routledge, 2022)
To the best of our knowledge, this is the first study to examine the risk spillover between Islamic and conventional banks in Malaysia. Given that Malaysia is one of the most influential countries for Islamic finance, it is important for market participants to determine the sources of risk spillovers in order to identify appropriate hedges for minimizing the risk linked to Islamic bank stocks. Nevertheless, the time-varying volatility dynamics of Islamic banks' equities remain understudied. This paper aims to fill this void in the existing literature. Employing different versions of the VAR-GARCH approach, we find a bidirectional volatility transmission relationship between Islamic and conventional banks in Malaysia. The analysis of time-varying correlations further shows that the average correlation between these stock indexes appears to be weak implying that investors holding assets in these sectors could successfully minimize the potential risk associated with their portfolios. Hence, the results have important implications for portfolio diversification and hedging strategies.
Keywords: Islamic banks; Conventional banks; Risk spillover; Malaysia; Volatility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|